Antigenic and immunogenic evaluation of permutations of soluble hepatitis C virus envelope protein E2 and E1 antigens. - Jannick Prentoe (Public Library of Science (PLoS), 2021)
Yearly, about 1.5 million people become chronically infected with hepatitis C virus (HCV) and for the 71 million with chronic HCV infection about 400,000 die from related morbidities, including liver cirrhosis and cancer. Effective treatments exist, but challenges including cost-of-treatment and wide-spread undiagnosed infection, necessitates the development of vaccines. Vaccines should induce neutralizing antibodies (NAbs) against the HCV envelope (E) transmembrane glycoprotein 2, E2, which partly depends on its interaction partner, E1, for folding. Here, we generated three soluble HCV envelope protein antigens with the transmembrane regions deleted (i.e., fused peptide backbones), termed sE1E2 (E1 followed by E2), sE2E1 (E2 followed by E1), and sE21E (E2 followed by inverted E1). The E1 inversion for sE21E positions C-terminal residues of E1 near C-terminal residues of E2, which is in analogy to how they likely interact in native E1/E2 complexes. Probing conformational E2 epitope binding using HCV patient-derived human monoclonal antibodies, we show that sE21E was superior to sE2E1, which was consistently superior to sE1E2. This correlated with improved induction of NAbs by sE21E compared with sE2E1 and especially compared with sE1E2 in female BALB/c mouse immunizations. The deletion of the 27 N-terminal amino acids of E2, termed hypervariable region 1 (HVR1), conferred slight increases in antigenicity for sE2E1 and sE21E, but severely impaired induction of antibodies able to neutralize in vitro viruses retaining HVR1. Finally, comparing sE21E with sE2 in mouse immunizations, we show similar induction of heterologous NAbs. In summary, we find that C-terminal E2 fusion of E1 or 1E is superior to N-terminal fusion, both in terms of antigenicity and the induction of heterologous NAbs. This has relevance when designing HCV E1E2 vaccine antigens.